An Analysis of Omenn Syndrome– A Rare Combined Immunodeficiency Syndrome (Indian Journal of Public Health Research & Development, 2021)
Omenn Syndrome is a rare combined immunodeficiency syndrome manifested mainly by generalisederythroderma, alopecia, loss of eyebrow and eye lashes, generalised oedema and metabolic disturbances.Poor prognosis is reported as it mimics the appearance of severe eczema and immunodeficiency and is undernoticed as there is presence of circulating lymphocytes. Understanding the guidelines of prompt diagnosiswill facilitate early treatment and improve prognosis.
Keywords: Omenn syndrome, treatment, guidelines, prognosis